Measurement of the inclusive isolated photon production cross section in pp collisions at √s = 7 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Pachmayer, Yvonne C.; Reygers, Klaus; Schicker, Rainer; et al. (The European physical journal. C, Particles and fields, 2019)
The production cross section of inclusive isolated photons has been measured by the ALICE experiment at the CERN LHC in pp collisions at a centre-of-momentum energy of √s = 7 TeV. The measurement is performed with the electromagnetic calorimeter EMCal and the central tracking detectors, covering a range of |η| < 0.27 in pseudorapidity and a transverse momentum range of 10 < p(T)(gamma) < 60 GeV/c. The result extends the p(T) coverage of previously published results of the ATLAS and CMS experiments at the same collision energy to smaller p(T). The measurement is compared to next-to-leading order perturbative QCD calculations and to the results from the ATLAS and CMS experiments. All measurements and theory predictions are in agreement with each other.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
ALICE Collaboration*: Shreyasi Acharya, Venelin Anguelov, Mesut Arslandok, Meike Danisch, Victor Feuillard, Peter Glässel, Jiyoung Kim, Minjung Kim, Markus Konrad Köhler, Yvonne C. Pachmayer, Klaus Reygers, Rainer Schicker, Marten Ole Schmidt, Johanna Stachel, Bernd Windelband [und 1009 weitere]
Gesehen am 25.05.2020